Analisis Kesalahan Dalam Menyelesaikan Soal Cerita Matematika Berbasis Gaya Kognitif Dikelas Xi Smk Asta Mitra Purwodadi Tahun Pelajaran 2016/2017 - Ari Wulandari, Enjang; , Dr. Sumardi, M.Si (2017)
Abstract This study aimed to describe: 1) errors experienced by students the field type dependent and independent field type in solving mathematical word problems. 2) Factors contributing to students' field type dependent and independent field type to make mistakes in solving math word problems. 3) How to completion student field type dependent and independent field type in solving mathematical word problems. This form of qualitative research, with qualitative descriptive research strategy. Subjects of research using sample selection aims (purposive sample). Data collection techniques used were: observation, testing methods, the method of interview. The validity of the data was done by using triangulation method. Analysis of the data is the data reduction, data presentation, and draw conclusions. The results of data analysis and discussion we concluded: 1) Students with cognitive style Field Independent category tend to make mistakes while Field Dependent fact likely to make errors of fact, misconceptions, incorrect operation, and error principle. 2) Causes of errors students who have cognitive style Independent Field is a mistake of fact that students are less thorough in completing the answer. While the cause of the error of students who have cognitive style Field Dependent (a) Type of factual errors that students are less thorough in completing the answer. (b) type of conceptual errors that occur on student misconceptions when it received an explanation from the teacher. (c) Type of operation errors that students do not pay attention to the teacher at the time explained. (d) Type of fault principle that students have never worked on a story about the type of matter linear program. 3) Remedies Fiel Type Dependent and Independent Fiel mode ie students with field independent cognitive style is the direct learning model (direct instruction) whereas field independent cognitive style of learning using the inquiry model with contextual approach. Keywords: error, error type, cognitive style, settlement